Pengembangan Media MONORAJA (Monopoli Aksara Jawa) untuk Siswa Sekolah Dasar - Syahbarina, Maulia (Mimbar Sekolah Dasar, 2017)
The background of this study is based on observations and interviews with class V teachers that students still have difficulty in understanding the letter of Java. Actions that have been done by teachers to overcome these problems have not been maximized, due to the limitations of tools and media. The type of this research is research and development with the developed product that is MONORAJA media (Monopoli Aksara Jawa) on Javanese language subject matter Java letter for elementary school student. The media were tested in 3 primary schools namely SDN Sadeng 01 Gunungpati, SDN 1 Lamuk Purbalingga, and SDN 2 Sinduraja Purbalingga. The results obtained from the validation of material experts, media experts, teacher practitioner questionnaire, and student assessment questionnaire. The result of validation by the first material expert is 97.71%, the second material expert is 98.5%, the validation by the media expert is 95%, the practitioner is 98%, and the student's appraisal is 96.36% This shows that MONORAJA media has been successful in development.